Strategi Guru dalam Penyampaian Materi Soal Cerita Matematika pada Siswa Sekolah Dasar - Mafdurotul Goliah; Miftahul Jannah; Muryani Muryani; Yuyu Yuhana (Universitas Batanghari Jambi, 2023)
This study aims to analyze the teacher's strategy in delivering grade IV math story problems in elementary schools. The research method used is descriptive qualitative research, with an empirical research design (Empirical Research). The population was taken from students of SD Unggulan Tahfizh Assabilillah and SDN Kemuning. The selected sample is fourth grade students from each elementary school. Data collection techniques used are observation, interviews, and documentation. The data analysis used is an inductive and continuous analysis. Data analysis in this study uses the stages of Miles and Huberman. The results of this study are three strategies used by the teacher in conveying story questions, while the results are 1) The teacher needs to open students' understanding of thinking concretely by including teaching aids; 2) Associating with everyday life; 3) Re-explaining the purpose of the story problems presented. So it was concluded that these three strategies could be used by teachers in conveying math story problems in class IV of SD Unggulan Tahfizh Assabilillah and SDN Kemuning.